Effect of Stem Cell Infusion Therapy on Sexual Function in Women with Type 2 Diabetes and Metabolic Syndrome: Post-Hoc Analysis of Randomized Controlled Trials. (1st August 2022) - Saltzman, R; Ripps, S; Balaji, N; Cabreja, M; Schulman, I; Khan, A; Golan, R; Hare, J; Ramasamy, R
ABSTRACT: Introduction: There is a growing interest in restorative therapies for sexual function, yet there exists a paucity of human research into potential therapeutic applications of stem cell therapy (SCT). Mesenchymal Stem Cells (MSCs) and their effect on sexual function have not yet been explored in women with Type 2 Diabetes Mellitus (DM) and Metabolic Syndrome (MetS). Objective: To determine the safety and efficacy of intravenous mesenchymal stem cell infusion therapy on sexual function in women with DM or MetS. Methods: Female participants enrolled in the ACESO (NCT02886884) and CERES (NCT03059355) clinical trials completed the Sexual Quality of Life Questionnaire-Female (SQOL-F). SQOL-F is a validated 18-item self-assessment questionnaire rated on a six-point scale ranging from "completely agree" to "completely disagree" in which higher scores reflect better sexual quality of life. Participants were enrolled in the trials based on diagnosis of DM or MetS, respectively. Intervention in both trials was peripheral intravenous infusion of allogeneic MSCs. Follow-up was for 1 year. Questionnaires were collected at baseline and 1-, 3-, 6-, and 12-months post-infusion. Participants received 20 or 100 million MSCs from either bone marrow (n=5) or umbilical cord (n=2). Results: Data was pooled from 7 women who participated in the two trials; 5 were from ACESO and 2 were from CERES. Three received high dose MSCs (100 million) and four received low dose (20 million) MSCs. The women in the ACESO trial received MSCs derived from healthy allogeneic donor bone marrow, and both women in the CERES trial received umbilical cord tissue derived MSCs. Median age was 73 [IQR=55-74] years. Six of the seven (86%) had past medical history of hypertension. Median SQOL score among all women at baseline was 30 [IQR=19-50], 25 [IQR=23-36] at 1 month, 34 [IQR=19-46] at 3 months, 29 [IQR=21-32] at 6 months, and 34 [IQR=26-49] at the end of 12 months. Improvements in SQOL from baseline through follow up did not meet level of statistical significance. Limitations of this study include the absence of a placebo-control group, the small sample size, and that sexual function was not a primary endpoint of the original trials. Conclusions: SQOL did not appear to improve following peripheral infusion of MSCs in women with DM or MetS, but nevertheless appears to be safe with no decline in sexual function over the following 1 year. Larger clinical trials with placebo-controls are needed to further investigate the optimal dose, source, and route administration of SCT to enact a meaningful change in sexual function in women with DM or MetS. Disclosure: Yes, this is sponsored by industry/sponsor: This work was supported by National Institutes of Health Grant R01 DK130991 and Clinician Scientist Development Grant from the American Cancer Society to RR. JMH is supported by National Institutes of Health grants 1R01 HL137355, 1R01 HL107110, 1R01 HL134558, 5R01 CA136387, and 5UM1 HL113460 and Soffer Family Foundation. Clarification: Industry funding only - investigator initiated and executed study Any of the authors act as a consultant, employee or shareholder of an industry for: JMH discloses a relationship with Vestion Inc. that includes equity, board membership, and consulting. Neither Longeveron, Vestion, or any other companies participated in the funding of this work. All other authors indicated no potential conflicts of interest.